Buchenwald : Zur europäischen Textgeschichte eines Konzentrationslagers - Pabst, Stephan (2022)
Buchenwald concentration camp was an international event. During the seven years that it existed, people from 30 nations were deported there, and after 1945, texts about the camp were written in the majority of the languages that they spoke. This volume conveys an impression of the camp's reach in European literature by looking at the few canonical texts by writers like Apitz, Semprún, Kertész, Adler, and Antelme, but also going beyond them.